Alzheimer's disease: An acquired neurodegenerative laminopathy. (3rd May 2016) - Frost, Bess
ABSTRACT: The nucleus is typically depicted as a sphere encircled by a smooth surface of nuclear envelope. For most cell types, this depiction is accurate. In other cell types and in some pathological conditions, however, the smooth nuclear exterior is interrupted by tubular invaginations of the nuclear envelope, often referred to as a "nucleoplasmic reticulum, " into the deep nuclear interior. We have recently reported a significant expansion of the nucleoplasmic reticulum in postmortem human Alzheimer's disease brain tissue. We found that dysfunction of the nucleoskeleton, a lamin-rich meshwork that coats the inner nuclear membrane and associated invaginations, is causal for Alzheimer's disease-related neurodegeneration in vivo . Additionally, we demonstrated that proper function of the nucleoskeleton is required for survival of adult neurons and maintaining genomic architecture. Here, we elaborate on the significance of these findings in regard to pathological states and physiological aging, and discuss cellular causes and consequences of nuclear envelope invagination.